The electrodeposition of compositionally modulated multilayer coatings for enhanced corrosion resistance - G. Chawa (1996)
The concept of electrodeposited multilayer coatings has been examined using both a dual and single bath process route. The effectiveness of an electrodeposition coating technique was initially investigated on the copper–nickel system. Compositionally modulated metallic coatings (CMMCs) were formed by the alternate electrodeposition of copper and nickel. Individual layer thicknesses were varied from 10 nm to 2 μm by close control of the plating current density with a computer assisted pulse plating facility. Following successful deposition of CMMCs using the copper–nickel system, investigations were concentrated on the zinc–nickel system on steel substrates again both dual and single bath techniques were utilised , the former to produce CMMCs of alternate zinc and nickel as well as layered structures of either zinc or nickel with a commercial zinc–nickel alloy. A single bath technique was used to produce compositionally modulated alloy multilayer coatings (CMAMCs) consisting of alternate layers of two compositions of zinc–nickel alloy. Conventional salt spray and more rapid electrochemical corrosion tests were carried out to assess the effectiveness of the layered coatings, as well as scanning electron microscopy and dispersive X-ray analysis to study the morphological and compositional changes in the coating structures. Results indicate the improvements of corrosion resistance of many of layered structures over similar (in thickness) conventional electrodeposited zinc coatings.